Influence of parents' behavior during the meal and on overweight in childhood - Karen Muniz Melo (Escola Anna Nery, 2017)
Abstract Objective: To assess the influence of parents' behavior during meals and on the overweight in childhood. Methods: Cross-sectional and analytical study, with a quantitative approach, performed with children aged between 12 and 59 months, belonging to the enrolled population of a Family Health Strategy team, in Montes Claros (MG). In order to collect data, it was used a questionnaire with sociodemographic variables related to food consumption and family influence over the eating habits. The anthropometric parameters of weight and height were assessed. We used the Student's t-test (p < 0.05) to compare the averages of the eating behavior of parents and the overweight in childhood. Results: 115 children participated. The overweight in childhood was statistically related to the behavior of parents during meals in the domains "model of sweets consumption" and "special meals". Conclusion: The family environment is associated with the formation of eating habits and the overweight in childhood.